Glypican-3 as a tumor marker for hepatocellular carcinoma - Amal A. Mohamed, Naglaa El-Toukhy, M. Magdi Atta, Salah M. Ahmed (Journal of Applied Pharmaceutical Science, 2013)
Hepatocellular carcinoma (HCC) is one of the most frequent cancers in the world.The burden of HCC has been increasing in Egypt with a doubling in the incidence in the past ten years. The prognosis of most patients is unsatisfactory due to rapid clinical deterioration after the initial diagnosis. Therefore, it is very important to detect HCC and the recurrence at its earlier period. Glypican-3(GPC3) is a cell-surface protein, which is a member of the heparan sulfate proteoglycan family. GPC3 was indentified in the serum of patients with HCC and can be used as a serological test for the diagnosis of HCC. The aim was to assess the value of serum GPC3 in Egyptian patients with HCC. This study was included 30 patients with HCC, 30 patients with liver cirrhosis and 20 healthy controls. For all groups we studied clinical data, image findings, serum alphafetoprotein(AFP) levels detected by enzyme immunoassay(EIA) kit and GPC3 gene expression was detected by real time polymerase chain reaction(PCR).Tumour characteristics were assessed including size, number and site. Tumour staging was done using Okuda &Tokyo staging systems.The data showed that HCC patients had a significantly higher mean GPC3 values (p=0.000)than both cirrhotics and healthy control groups. GPC3 has a positive significant correlation with tumour size (p=0.015)and Tokyo staging system(p=0.047).GPC3 could be a useful diagnostic & prognostic marker for detection of HCC.
Keywords: Hepatocellular Carcinoma, Glypican-3, Alpha-fetoprot